2021
DOI: 10.1161/strokeaha.120.032430
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Age and Alberta Stroke Program Early Computed Tomography Score 0 to 5 on Mechanical Thrombectomy Outcomes: Analysis From the STRATIS Registry

Abstract: Background and Purpose: This study investigates clinical outcomes after mechanical thrombectomy in adult patients with baseline Alberta Stroke Program Early CT Score (ASPECTS) of 0 to 5. Methods: We included data from the STRATIS Registry (Systematic Evaluation of Patients Treated With Neurothrombectomy Devices for Acute Ischemic Stroke) from patients who underwent mechanical thrombectomy within 8 hours of symptom onset and had available ASPECTS data ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 33 publications
2
21
0
Order By: Relevance
“…Our study did not show a significant difference in rates of 90 day mortality and sICH between low versus higher ASPECTS groups. This is similar to the results from the MR CLEAN trial25 but different from the HERMES analysis and STRATIS registry data 3 22. This is a conflicting yet reassuring finding from this study on the safety outcomes in low ASPECTS patients treated with EVT.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Our study did not show a significant difference in rates of 90 day mortality and sICH between low versus higher ASPECTS groups. This is similar to the results from the MR CLEAN trial25 but different from the HERMES analysis and STRATIS registry data 3 22. This is a conflicting yet reassuring finding from this study on the safety outcomes in low ASPECTS patients treated with EVT.…”
Section: Discussionsupporting
confidence: 75%
“…However, there are conflicting data on these topics in the literature 4 19 20. For example, data from the HERMES meta-analysis showed that patients with ASPECTS 3–5 benefited from EVT, while other non-randomized studies showed discrepant findings, leading to more uncertainties in the field 5 7 21–23. Recently, RESCUE JAPAN LIMIT randomized 203 patients with ASPECTS 3–5 onset into EVT with medical therapy versus medical therapy alone.…”
Section: Discussionmentioning
confidence: 99%
“…The Systematic Evaluation of Patients Treated with Neurothrombectomy Devices for Acute Ischemic Stroke (STRATIS) registry looked at the impact of age in 57 patients with CT-ASPECTS 0–5 who underwent thrombectomy. Successful reperfusion (≥TICI 2b) was achieved in 85.5% (47/55) in the ASPECTS of 0 to 5 group; however, functional independence was only achieved in 28.8% (15/52), with no patients >75 years of age achieving good outcomes ( 13 ). This implies that a more precise method of patient and imaging selection is required in patients with expected large core infarcts.…”
Section: Is Dwi-aspects An Appropriate Substitute For Volumetric Anal...mentioning
confidence: 99%
“…Similar findings were seen in DEFUSE-3 for functional independence at 90 days, significantly favoring the endovascular arm compared to medical therapy with a risk ratio of 2.67 (95% CI, 1.6–4.48). The risk ratio for the subgroup of ischemic core volume of 10–25 ml was 4.4 (95% CI, 1.41–20.33) and ischemic core volume 25–70 ml was 3.06 (95% CI, 1.01–13.52) ( 13 ). These two landmark trials indicate that a selected group of patients with a core volume of <70 ml is favorable with EVT.…”
Section: Is Dwi-aspects An Appropriate Substitute For Volumetric Anal...mentioning
confidence: 99%
“…For large vessel occlusive strokes, reperfusion therapy is the best treatment modality. Therefore, many clinical trials have focused on symptomatology, imaging, and temporal interventions to improve the clinical prognosis of patients and guide treatment choice (2)(3)(4). Recently, few studies have focused on the prognostic impact of vital signs in patients with ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%